Rare earth and bird cartridge compost in coffee change development - Freire, Luiz Gustavo Rosa; Santini, Paula Tristão; Silva, Mariana Fávero; Maciel, Anna Lygia de Rezende (Revista Agrogeoambiental, 2020)
The use of alternative composting, such as animal carcasses, is viable for the final disposal of these wastes. Rare Earth Elements (REEs) are a homogeneous group of 17 chemical elements in the periodic table that are essential for many industries. The objective of this work was to evaluate the influence of poultry carcass compost and REEs on the development of coffee seedlings. The study was carried out at IFSULDEMINAS – Campus Muzambinho, from July 2018 to January 2019. The experimental design was a randomized complete block design (DBC) in a 3x5 factorial scheme, with four replications and 21 plants per plot central. The treatments consisted of different concentrations of poultry carcass compost (0, 150 and 300 L m-3) and dosages of REEs (mix 1, 2, 3, 4 and 5). Mixing was performed on the seedlings when they reached the second leaf pair. Evaluations were performed at 180 days after sowing, evaluated by: plant height, stem diameter, leaf number and leaf area. The data obtained were submitted to variance analysis using the SISVAR software, and the significant difference between treatments was determined by the F test. Detecting differences between treatments by the Scott-Knott test. It was observed that the 150 m-3 dosage of poultry carcass compost showed a significant increase in plant height (16.68 cm), stem diameter (3.29 cm) and leaf area (248.99 cm²). However, for the variable number of leaves, no significant difference was observed between the procedures. The use of poultry carcass compost at 150 liters m-3 promotes greater seedling development. The addition of REEs at the doses used does not affect the development of coffee plants.